Corrosion Behavior of Chromium Conversion Coated AZ91C Magnesium Alloy in Sodium Borate and Sodium Chloride Aqueous solutions (The International Journal of Engineering & Information Technology (IJEIT), 2024)
A chromium containing film was deposited on the surface of the investigated AZ91C magnesium alloy by chemical conversion process. The microstructure and surface morphology of the as- received and coated alloys were initially characterized by optical microscope. The corrosion behavior of AZ91C before and after coating was studied through weight loss technique by immersion in 3.5% NaCl and borate solutions at various concentrations and pH values. Surface corrosion products and passivation films were analyzed by X-ray diffraction. The obtained results showed that AZ91C coated with chromium conversion coating exhibits enhanced corrosion resistance, furthermore X-ray diffraction revealed that corrosion damage was mainly caused by formation of crystalline phase Mg(OH)2. The addition of borate with different concentration enhanced the protection with efficiency of 86% recorded at 0.2N sodium borate concentration and 3.5% NaCl.Corrosion behavior